Efecto de la temperatura en austenización simple y doble del tratamiento térmico convencional del acero para herramientas AISI D2 sobre la microestructura, dureza y tenacidad - Becerra Avila, Jorge Gerardo (2019)
The effect of temperature on microstructure, hardness and toughness on the U-noted notch of heat-treated AISI D2 steel was studied in thermal cycles corresponding to Simple Austenization at 850°C, 950°C and 1100°C and Double Austenization at 850-850°C, 850- 950oC, 850-1100°C, 950-850°C, 950-950°C, 950-1100°C, 1100-850°C, 1100-950°C and 1100-1100°C. Prismatic specimens of 0.6 x 0.6 x 5.5 cm were prepared and heat treated on an L75 Series Premium Dilatometer, temperature control and cooling speeds of the thermal cycle was performed using the dilatometer software. The specimens were subsequently prepared under ASTM E-23 for the Charpy U-not test and where the hardness was measured in HV20 under ASTM E 92. Under ASTM E-93, samples were prepared for metallographic analysis and grain size was determined using optical microscopy in a first stage a representative mesh of the metal grain areas was determined with CorelDRAW x7 software, Areas were subsequently determined using Pro Plus Image based on the scale of the photomicrograph. Areas were adjusted to a Log-normal model with Origin 2018 software, thus determining the normal distribution of areas and ASTM grain diameter, in accordance with ASTM E-112. The results determined that the simple austenization temperature increased the hardness significantly from 222.25 HV20 (850°C) to 302.13 HV20 (1100°C) in double austenization, values rose from 213.5 HV20 (850-850ºC) to 405.63 HV20 (1100- 1100°C) determining a significant effect on the first temperature of austenization. The tenacity at the KVC notch (J/cm2) with U notch decreased as the temperature in single and double austenization austenization was increased, for the Simple decreases from 12.43 J/cm2 to 5.67 J/cm2 and for the double the results of up to 14.66 J/cm2 maximum and 4.71 J/cm2 at least. On the other hand, the increase in carbid solution was confirmed by increasing the number of ASTM grain. The double austenization treatment allowed the dissolution of alloy carbides during the first treatment, while the second austenization at low temperatures gave a finer grain of austene, increasing the ASTM number because the carbides did not dissolved sites provide abundant nucleation sites for austeenite and during the second austenization treatment promotes the finest grain size.